Ultraviolet light-induced crosslinking of mRNA to proteins. - Greenberg, J R (1979)
Irradiation of intact or EDTA-dissociated L-cell polyribosomes with 254 nm UV light at doses of 1-2 x 10(5) ergs/mm2 extensively crosslinks mRNA to proteins. The crosslinked mRNA-protein complexes can be isolated on the basis of buoyant density in urea-containing CS2SO4 gradients that dissociate non-covalent complexes. Crosslinking of mRNA can also be assayed by phenolchloroform extraction. mRNA recovered from the crosslinked complexes by digestion with proteinase K has the same electrophoretic mobility in polyacrylamide gels as unirradiated mRNA. Therefore, irradiation does not either crosslink RNA molecules to RNA molecules or break phosphodiester bonds. With these methods it has been found that more than 70% of high molecular weight polydisperse mRNA, but only 25-40% of histone mRNA, can be crosslinked to protein. On the basis of buoyant density the histone mRNA-protein complex had a protein content of 26%, whereas the mean protein content of most non-histone mRNA-protein complexes was 65%. It is concluded that most mRNA in polyribosomes is in close contact with proteins, and that histone mRNA can be crosslinked to many fewer proteins that most other mRNAs.